(untitled) (El-Wahat Journal for Research and Studies, 2025)
This Work Focuses On The Driving Forces In Yasmina Khadra’s Novel, The Sirens Of Bagdad. Semiotic Analysis Allows Us, First Of All, To Examine And Structure The Relationships Between The Driving Forces In The Novel. It Is, Secondly, To Analyze The Relationship Between The Sender Being The Authority Which Charges The Hero With His Quest, And The Hero Who Ensures Its Accomplishment. Although He Carries Out The Action Assigned To Him, The Subject Does Not Benefit From His Quest And He Appears Manipulated By Forces Which Condition His Mind And His Way Of Seeing The World. keywords: Manipulation, Actant, Action, Semiotic, Narratif Scheme.